1998
DOI: 10.1021/bi972337s
|View full text |Cite
|
Sign up to set email alerts
|

The MotA Transcriptional Activator of Bacteriophage T4 Binds to Its Specific DNA Site as a Monomer

Abstract: During bacteriophage T4 middle mode gene expression, the MotA transcription factor binds to T4 middle promoters at a -30 mot box consensus sequence to allow activation. Previous binding studies showed that MotA forms multiple gel-shifted complexes with DNA, and structural evidence suggested that MotA dimerizes upon DNA binding. We have shown that a short (13 bp) mot box DNA substrate binds MotA protein but fails to form slower migrating complexes. Therefore, the slower migrating complexes in gel shift assays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
16
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
(32 reference statements)
4
16
0
Order By: Relevance
“…This provided confidence that the FeBABE analyses were reporting the relevant position of MotA within the -appropriated complex. In addition, the positions of the cleavages were consistent with the binding of a monomer of MotA (rather than a dimer or other multimers) within the transcription complex; previous work has indicated that MotA alone binds as a monomer to the MotA box (45).…”
Section: Selection Of Mota Residues For Conjugation With Febabe-insupporting
confidence: 71%
See 1 more Smart Citation
“…This provided confidence that the FeBABE analyses were reporting the relevant position of MotA within the -appropriated complex. In addition, the positions of the cleavages were consistent with the binding of a monomer of MotA (rather than a dimer or other multimers) within the transcription complex; previous work has indicated that MotA alone binds as a monomer to the MotA box (45).…”
Section: Selection Of Mota Residues For Conjugation With Febabe-insupporting
confidence: 71%
“…6B1). This has been observed previously when analyzing MotA binding by EMSA (46) or by fluorescence anisotropy (45). Although MotA binds to the MotA element as a monomer (45), EMSAs suggest that multimers of MotA associate with the protein-DNA complex as the concentration of MotA increases.…”
Section: Selection Of Mota Residues For Conjugation With Febabe-insupporting
confidence: 68%
“…Some transcriptional regulators bind their target sites as monomers (e.g., members of the AraC family and MotA from bacteriophage T4) (11,17), or as homomultimers (e.g., LacI, H-NS, and the LysR family) (4,6,34,52). Heteromeric transcriptional activators are unusual in bacteria but have been reported, such as the dimer of integration host factor, IHF-␣␤, the dimer of the regulator of capsular biosynthesis, RcsBA, and dimers of the nucleoprotein H-NS with another nucleoprotein, Hha or StpA (15,57).…”
mentioning
confidence: 99%
“…This promoter binding in the presence of AsiA requires the DNA-binding region of the a subunits of RNA polymerase, suggesting that with a long enough incubation, a-DNA contacts can eventually compensate for the lack of contacts between s 70 region 4 and the 235 DNA element (Orsini et al, 2001). The T4 MotA protein is a transcription activator that binds as a monomer (Cicero et al, 1998;Li et al, 2002) to the MotA box element (Brody et al, 1983;Guild et al, 1988;Hinton, 1991;Schmidt & Kreuzer, 1992) with an apparent dissociation constant of 100-200 nM (Cicero et al, 1998;Sharma et al, 1999a). MotA also interacts with s 70 (Gerber & Hinton, 1996;Pande et al, 2002).…”
mentioning
confidence: 99%